Development of Competitive ELISAs Suitable for Detection of Recombinant Human Growth Hormone in Illegal Nutritional Supplements - L. Karamonová; B. Procházková; M. Volný; A. Nemeškalová; D. Sýkora; M. Kuchař; L. Fukal; B. Holubová (Journal of Analytical Methods in Chemistry)
The use of human growth hormone (hGH) by athletes remains widespread despite being banned by the World Anti-Doping Agency (WADA). Current commercial ELISA kits for the determination of hGH are predominantly based on the sandwich format of this method, which allows the analysis of the whole hGH molecules, but not their fragments. The abuse of these fragments by athletes is the current trend in doping. Therefore, a competitive ELISA format is needed; however, only a limited number of kits on the market are based on this principle. Furthermore, these kits are designed to detect and quantify hGH only in blood plasma, serum or tissue cultures. When analysing a nutritional supplement containing hGH using one of these ELISA kits, a false negative result was observed. In the present work, two competitive ELISA methods for the detection of hGH in illegal nutritional supplements were developed. The development of the methods involved the selection of suitable immunoreagents and their combinations with subsequent optimisation of the conditions for their use. The methods were then characterised (with LOD 0.4 and 18.4 ng/mL, according to the primary antibody) and applied to analyse real nutritional supplements. In all 34 samples suspected of containing hGH, the hormone was detected using both ELISA methods and subsequently confirmed by LC-UV and LC-MS. Therefore, the newly developed ELISA methods could become a valuable tool for the police in identifying illegal preparations.